Was the fuss overblown? (Nature, 2003)
To the friends and relatives of the 800-plus people slain by severe acute respiratory syndrome (SARS), this might seem like a callous question. But SARS barely registers a blip in the annual body count caused by infectious disease. Influenza is likely to kill up to half-a-million people in 2003, whereas the death tolls from malaria, tuberculosis and AIDS will each run to seven figures. So, when the outbreak is put into perspective, was the panic over SARS really warranted?